Línea de investigación: la práctica de enfermeria en el contexto social (1998)
ABSTRACT: This article shows the line of research on the practice of nursing in the social context. It states the background on making the research group and the conceptual and methodology approach. Then, finished and on – going research are described as well as results of research group, concerning publications and participation in scientific events.